New generation modem for future data transmission systems. Part 1 - Yu. M. Veshkurtsev (Омский научный вестник)
New methods of signal modulation and demodulation implemented at the level of invention in the modem structure are considered. Theoretically there are investigated and statistical modeling confirmed noise immunity of the modem when working in the channel without interference.